Development and Validation of a Branding Model in Social Media Considering Users’ Motivations for Content Creation and Sharing - Jafari , Parisa; Fakhimi Azar, Sirous; Iranzadeh, soleiman; Bodaghi Khajeh Noubar, Hossein (Business, Marketing, and Finance Open, 2025)
This study aims to develop and validate a branding model in social media that considers users' motivations for content creation and sharing, integrating content marketing strategies, brand competitiveness, customer trust, and brand value. This research employs an exploratory mixed-methods approach, consisting of qualitative and quantitative phases. In the qualitative phase, semi-structured interviews were conducted with 11 marketing experts to identify key branding factors, analyzed using thematic analysis and coding methods. The quantitative phase involved surveying 384 social media users through a researcher-designed questionnaire based on qualitative findings. Structural equation modeling (SEM) was employed to validate the proposed branding model, assessing relationships between content marketing strategy, content creation, brand competitiveness, customer experience, and brand trust. Results indicate that content marketing strategy significantly influences content creation and sharing (β = 0.85, t = 9.01) and customer experience management (β = 0.72, t = 8.41). Content creation positively impacts brand value creation (β = 0.36, t = 2.42), while customer experience enhances brand value (β = 0.51, t = 6.66). Brand value creation strengthens brand competitiveness (β = 0.88, t = 9.37) and customer satisfaction and trust (β = 0.79, t = 8.65). Furthermore, brand competitiveness (β = 0.58, t = 6.05) and customer satisfaction and trust (β = 0.36, t = 2.94) positively influence branding success in social media. The model achieved an acceptable fit, with RMSEA = 0.033, SRMR = 0.038, and GFI, NFI, and TLI all exceeding 0.90. The findings highlight the central role of user engagement in social media branding, emphasizing the importance of content marketing strategies, brand competitiveness, and trust-building mechanisms. Effective branding in social media requires interactive and personalized engagement strategies that align with user motivations for content creation and sharing.